Analisis Hubungan Modal Intelectual (Intellectual Capital) Terhadap Kinerja Keuangan BUM Desa Di Kecamatan Seberida Kabupaten Indragiri Hulu - Mira Sandrana; Ahmad Rifai; Kausar Kausar (JIP ( Jurnal Industri dan Perkotaan ), 2020)
Intellectual Capital is applied experience, organizational technology, customer relations, and expertise that can create a competitive advantage for BUM Desa which is aimed at administrators in managing BUM Desa, and to what extent affects the management of Intellectual Capital on the performance of BUM Desa, which can be managed with innovation, collaboration and good human resources. owned. This study aims to describe the performance of BUM Desa administrators with the suitability of BUM Desa financial reports conducted in Titian Resak Village, Seresam Village ,and Petala Bumi Village, Seberida District, Indragiri Hulu Regency. The method used in this research is the survey method and research respondents. The results of this study indicate that intellectual capital and financial performance have a very tied and balanced relationship. BUM Desa, Seberida Subdistrict, which has the highest variable, is relational capital, which shows the attitude of the BUM Desa management and leadership helping each other. The highest dimension is relationships with customers who receive criticism and suggestions from BUM Desa customers. Based on the financial performance of BUM Desa, ROA, which has an average of 1.38 with a very good category. ROE (Return On Equity) which has an average value of 8.48% in the "good enough" category. The ratio of BOPO (Operational Costs and Operating Income) which has an average value of 87.88% is in the "very good" category. So that BUM Desa has high intellectual capital, its financial performance is also good and those that have low value, the financial performance is not good.